Improving Students' Spatial Ability by Using Macromedia Flash on Geometry Materials - Yani, Muhammad; Rosma, Fatemah (Universitas Malikussaleh, Aceh Utara, Indonesia, 2020)
Every student must have and develop spatial abilities to be successfull in learning geometry. The rapid development of technology also allows teachers to use macromedia flash as an alternative in developing and improving students' spatial abilities. This study aimed to determine and describe the improvement of the students' spatial ability after getting geometry material by using macromedia flash at MTsN Model Banda Aceh. This research used a quantitative approach with a quasi-experimental design and one group pretest posttest design. The population of this study was all students of class VIII MTsN Model Banda Aceh with random sampling as the sample selection techniques so that the selected sample was the students of class VIII-5. The data collection in this study was carried out using a spatial ability test consisted of pretest and posttest questions. The gained data were analyzed with SPSS version 17 with paired sample t-test and percentage. The results showed that there was an improvement in students' spatial ability after having geometry material learning by using macromedia flash at MTsN Model Banda Aceh. Besides, the improvement of students' spatial ability based on indicator of perception spatial was 61.1%, mental rotation indicator was 55.6%, and indicator ofÂ visualization spatial was 66.7%.